(untitled) (Economics and region, 2022)
The article is devoted to the assessment of the competitiveness of hotel business enterprises. It was found out that in their research, scientists divide the methods of assessing competitiveness into separate groups, among which the most common are: quantitative, qualitative, matrix, graphic methods, etc. It is noted that each of them has its own advantages and disadvantages, and the expediency of application depends on the purpose of the study, the conditions of operation of this or that business entity. We have assessed the competitiveness of the limited liability company "Hotel Management Group", which includes the premium hotel and health complex "Mirotel Resort & Spa", the villa "Hrystyna" and the hotel "VESNA", which are located in the heart of the resort city of Truskavets. In the work, the calculation of the integral indicator of competitiveness assessment was carried out based on the differential method, which is based on the construction of the competitiveness matrix and the determination of the competitiveness index, as well as the graphic construction of the competitiveness polygon for the evaluation of the competitiveness of hotel business enterprises. Among the large number of competitors of "Hotel Management Group" we will select those that have the most significant influence on the activity of the investigated enterprise, and are also in the same price category, and we will divide them into three groups, since the enterprise has three different hotels in its composition. At the same time, the selection of parameters will be carried out with the help of a well-known site in the field of tourism, Booking.com, where, on the basis of a survey of hotel visitors, their evaluation was carried out and the corresponding evaluation parameters were indicated. We will also supplement them with other parameters that allow us to analyze the competitiveness of hotel business enterprises and compare them with each other. This made it possible to conduct an analysis of the researched enterprise with its competitors in 11 categories, which made it possible to determine the advantages and bottlenecks in the business entity’s activities.